Effect of resistive load characteristics on the performance of Organic Rankine cycle (ORC). (1st May 2022) - Jin, Yunli; Gao, Naiping; Zhu, Tong
Abstract: The effects of various organic Rankine cycle (ORC) components, such as evaporator, expander and condenser on the performance of the system have been extensively studied. However, only a handful of studies have focused on studying the influence of external load characteristics. A small-scale ORC test rig of 3 kW e was constructed to experimentally investigate the effect of resistive load on the performance of the system. In order to achieve this, the study combined the thermodynamic method with electrical analysis. The results showed that the increase in output power caused a simultaneous increase in rotational speed, torque and inlet pressure of the expander under constant load resistance conditions. However, the fluid mass flow rate only affected the expander's inlet pressure. The decrease in load resistance increased the expander's inlet pressure and torque, and reduced the superheating and rotational speed. The influences of load resistance on the isentropic efficiency and net efficiency were mainly thorough the expander's inlet pressure and superheating. The net efficiency also benefited from the ideal cycle efficiency due to that decreasing load resistance enlarged the enthalpy drop of expander. The effects of load resistance on performance parameters were restricted by the mass flow rate of the fluid. Highlights: A small-scale ORC test rig with scroll expander and resistive load is established. Effects of resistive load on operating parameters are presented. Influences of resistive load on system performance are obtained. Ways of load resistance affecting efficiency are explored. The interaction between resistive load and fluid mass flow rate is revealed.